MODEL TABUNGAN SAMPAH SEBAGAI UPAYA ALTERNATIF DALAM MENANGANI PERMASALAHAN ANAK JALANAN - AA, Subijanto; Khotijah, Khotijah; Yunita, Fresthy Astrika (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2015)
The purpose of this empowerment is to improve the ability of street children such as street musicians in increasing their income and also handling of waste / garbage in Surakarta. Managing street children holistically by considering various dimensions such as development of the community, characteristics of the community and the applied model will also produce a long-term impact. The methode used in this empowerment is participatori rurall appraisal by involving elemenst such as street children as a waste / garbage collector as a container / receiver, youth organization as a supervisor, and village officials as a protector. Garbage deposited will be recorder by the garbage collectors and accumulated at the end of the month. Therefore the money collected can be an additional earnings for them (street children). Evaluation is done every three months by youth organization and reported to the vilage officials. Evaluation of the first three months, there is still necessary guidance needed for the street children in order to remain diligent in carrying out their program. Empowerment in the Surakarta region particularly Nusukan and Semanggi villages has the potential to be applied also for housewives and teenagers.Â  Â